A Miss Kayapó: ritual, espetáculo e beleza - André Demarchi (Journal de la Société des Américanistes)
The present article proposes an ethnographic interpretation of the event called « Miss Kayapó », a Beauty Contest, whose participants are indigenous women from the Mebêngôkre (Kayapó) people, located in the Amazon forest, who speak a Jê language. Held in the city of São Félix do Xingu, in the State of Pará (Brazil), before a large number of indigenous and non-indigenous people, the Beauty Contest is an important ritual to understand the inter-ethnic relations between the contemporary Mebêngôkre and the other Brazilian inhabitants of the region. The idea here is to analyze the aesthetical and ritual forms of appropriation mobilized by the group, as well as the ways by which imagery control is exerted by indigenous peoples in the Contest. Another aim is to ethnographically describe the different editions of the Contest, in order to highlight the transformations occurred both in the body techniques apprehended by the candidates, and in the creation and composition of their costumes. The final proposal is to understand the ritual production of Miss Kayapó as a complex character, who holds the ability to embody different aesthetic perspectives.